Analisis Studi Kelayakan Bisnis pada Pengembangan UMKM Usaha Tempe Pak Iwan Bandung ditinjau dari Aspek Produksi, Aspek Pemasaran dan Aspek Keuangan - Eka Purwanda; Raden Willa Permatasari (Jurnal Multidisiplin Madani, 2022)
The culinary business is the biggest business choice because the demand is large, everyone needs to eat and drink, so this sector continues to experience increasingly rapid development. This study aims to determine the business feasibility of the Tempe Pak Iwan Bandung business, from the production aspect, marketing aspect and financial aspect. The results showed that based on the production aspect, marketing aspect and especially on the financial aspect, this Tempe business was said to be feasible with a project life of 5 years at a discount rate of 20%. The analysis of the eligibility criteria resulted in a Payback Period (PP) of 1 year and 8 months, a Net Present Value (NPV) of Rp. 1,077,541,937, a Profitability Index (PI) of 2.6 and an Internal Rate of Return (IRR) of 66%.